ANÁLISE DA INTERDEPENDÊNCIA DO CAPITAL PSICOLÓGICO, PERCEPÇÕES DE SUPORTE E BEM-ESTAR NO TRABALHO - Souza, Warton da Silva (2011)
Given the complexity in the work environment that requires greater commitment from its occupants and a growing demand for performance of these individuals, this study analyzed the interdependence of some variables of organizational behavior by testing a conceptual model composed of psychological capital, support perceptions and well-being at work. The participants were 152 workers who worked in the North (Tocantins) and Southeast (São Paulo) in public and private organizations. As an instrument for data collection was used a self-administered questionnaire composed of six scales measuring the variables of the study. This study set out to present, interpret and discuss the relationships between variables, and also test hypotheses regarding the proposed conceptual model through a cross-cutting research with a quantitative approach, whose data were analyzed by applying techniques of parametric statistics (descriptive statistics calculations: mean, standard deviation, test t and correlation; multivariate statistical calculations: analysis of multiple linear regressions hierarchical and stepwise) using the SPSS software, version 18.0. The results showed that the levels of the three dimensions of well-being at work are directly impacted by support perceptions (social work and organizational). It was confirmed also the psychological capital as a predictor of the perceptions of direct support (social work and organizational). Finally, this study has shown that workers with a high psychological capital tend to perceive support, both social and organizational work and, therefore, workers who perceive support (social and organizational work) tend to maintain links with their work and their employing organization, which represent well-being at work.